1995
DOI: 10.1007/bf01874758
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of the 3′-terminal region of the RNA of a mite transmitted potyvirus fromHordeum murinum L.

Abstract: The 3026 nucleotides upstream of the 3'-polyadenylated tract of a mite transmitted virus from Hordeum murinum L. were cloned and sequenced, and portions of the sequence were expressed in Escherichia coli. Sequence comparisons with wheat streak mosaic virus (WSMV), Agropyron mosaic virus (AgMV) and Hordeum mosaic cirus (HoMV), three mite transmitted potyviruses, and potato virus Y (PVY), the type member of the genus Potyvirus, revealed that the virus is probably a potyvirus, but distinct from WSMV, AgMV, HoMV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Bruno by mechanical transmission. BrSMV-Hm (Schubert & Rabenstein, 1995 ), BrSMV-11-Cal (Huth et al ., 1995 ; Götz & Maiss, 1995 ) and AgMV-Asl (Schubert & Rabenstein, 1995 ) were maintained by mechanical transmission in wheat cv. Alcedo.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruno by mechanical transmission. BrSMV-Hm (Schubert & Rabenstein, 1995 ), BrSMV-11-Cal (Huth et al ., 1995 ; Götz & Maiss, 1995 ) and AgMV-Asl (Schubert & Rabenstein, 1995 ) were maintained by mechanical transmission in wheat cv. Alcedo.…”
Section: Methodsmentioning
confidence: 99%
“…However, identification of these Eurasian isolates as WSMV was based mainly on biological properties such as host range, symptom expression and/or transmission by eriophyid mites. Because BrSMV also is transmitted by eriophyid mites, causes a similar disease on many of the same hosts as WSMV, and occurs in Europe (Milicic et al ., 1980 , 1982 ; Huth et al ., 1995 ; Götz & Maiss, 1995 ; Schubert & Rabenstein, 1995 ), biological properties alone are not sufficient to authenticate Eurasian isolates as WSMV. In fact, one putative WSMV isolate from Germany (Rabenstein et al ., 1982 ) was later shown by sequencing to be BrSMV (Schubert & Rabenstein, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…WSMV was also reported from wheat in Syria (Makkouk and Kumari 1997), western Poland (Je_ zewska and Wieczorek 1998), western Slovakia (Kúdela et al 2008), the Burgundy region of France (Gadiou et al 2009;Rabenstein et al 2008), northern Italy and Tuscany (Credi et al 1997;Gadiou et al 2009;Rabenstein et al 2008) and Czech Republic (Gadiou et al 2009;Rabenstein et al 2002). Rabenstein et al (1982) reported WSMV infection of Bromus sterilis L. (sterile brome) and Hordeum murinum L. (false barley) in Germany, but later it had been designated to be a BrSMV infection (Schubert and Rabenstein 1995).…”
Section: Eurasiamentioning
confidence: 99%
“…Brome streak mosaic virus was first isolated in the former Yugoslavia in 1977 from Bromus mollis L. (soft brome) and H. murinum (Milicic et al 1980(Milicic et al , 1982. Since then, BrSMV has been reported from B. sterilis and H. murinum in Germany (although originally misidentified as WSMV) (Rabenstein and Stanarius 1981;Rabenstein et al 1982;Schubert and Rabenstein 1995) and from barley crops in France (Huth et al 1995). In 2008, BrSMV was detected in Hungary, infecting an invasive weed species Cyperus esculentus L. (yellow nutsedge) (Takacs et al 2008).…”
Section: Brome Streak Mosaic Virus (Brsmv)mentioning
confidence: 99%
“…On the basis of its transmission, it is grouped together with wheat streak mosaic virus (WSMV), agropyron mosaic virus (AgMV), hordeum mosaic virus (HorMV), and oat necrotic mottle virus (ONMV) into the newly proposed genus Rymovirus within the family Potyviridae (Zagula, 1992 (Paliwal and Tremaine, 1976;Salm et al, 1993 (Sambrook et al, 1989 (fig 3). Using the CLUSTAL 4 option of the DNASIS software (Hitachi), the 3 mite-transmitted Potyviridae WSMV (Niblett et al, 1991), BrSMV (Schubert and Rabenstein, 1995) and RgMV as well as the aphid transmitted PVY (Robaglia et al, 1989) were grouped on the basis of the na sequences of their cp (fig 4). It (Carrington and Dougherty, 1988).…”
Section: Introductionmentioning
confidence: 99%